AMF species do matter: Rhizophagus irregularis and Funneliformis mosseae affect healthy and PVY-infected Solanum tuberosum L. in a different way - Deja-Sikora, Edyta; Werner, Klaudia; Hrynkiewicz, Katarzyna (Frontiers in Microbiology, 2023)
Arbuscular mycorrhizal fungi (AMF) were documented to positively influence plant growth and yield, which is extremely important for the production of many crops including potato. However, the nature of the interaction between arbuscular mycorrhiza and plant virus that share the same host is not well characterized. In this study, we examined the effect of different AMF, Rhizophagus irregularis and Funneliformis mosseae, on healthy and potato virus Y (PVY)-infected Solanum tuberosum L. The analyses conducted included the measurement of potato growth parameters, oxidative stress indicators, and photosynthetic capacity. Additionally, we evaluated both the development of AMF in plant roots and the virus level in mycorrhizal plants. We found that two AMF species colonized plant roots to varying degrees (ca. 38% for R. irregularis vs. 20% for F. mosseae). Rhizophagus irregularis had a more positive effect on potato growth parameters, causing a significant increase in the total fresh and dry weight of tubers, along with virus-challenged plants. Furthermore, this species lowered hydrogen peroxide levels in PVY-infected leaves and positively modulated the levels of nonenzymatic antioxidants, i.e., ascorbate and glutathione in leaves and roots. Finally, both fungal species contributed to reduced lipid peroxidation and alleviation of virus-induced oxidative damage in plant organs. We also confirmed an indirect interaction between AMF and PVY inhabiting the same host. The two AMF species seemed to have different abilities to colonize the roots of virus-infected hosts, as R. irregularis showed a stronger drop in mycorrhizal development in the presence of PVY. At the same time, arbuscular mycorrhiza exerted an effect on virus multiplication, causing increased PVY accumulation in plant leaves and a decreased concentration of virus in roots. In conclusion, the effect of AMF-plant interactions may differ depending on the genotypes of both symbiotic partners. Additionally, indirect AMF-PVY interactions occur in host plants, diminishing the establishment of arbuscular mycorrhiza while changing the distribution of viral particles in plants.